Elucidating the Impact of Mg Substitution on the Properties of NASICON‐Na3+yV2−yMgy(PO4)3 Cathodes. (27th August 2021) - Ghosh, Subham; Barman, Nabadyuti; Gonzalez‐Correa, Eliovardo; Mazumder, Madhulika; Zaveri, Aryan; Giovine, Raynald; Manche, Alexis; Pati, Swapan K.; Clément, Raphaële J.; Senguttuvan, Premkumar
Abstract: Vanadium multiredox‐based NASICON‐Na z V2− y M y (PO4 )3 (3 ≤ z  ≤ 4; M = Al 3+, Cr 3+, and Mn 2+ ) cathodes are particularly attractive for Na‐ion battery applications due to their high Na insertion voltage (>3.5 V vs Na + /Na 0 ), reversible storage capacity (≈150 mA h g −1 ), and rate performance. However, their practical application is hindered by rapid capacity fade due to bulk structural rearrangements at high potentials involving complex redox and local structural changes. To decouple these factors, a series of Mg 2+ ‐substituted Na3+ y V2− y Mg y (PO4 )3 (0 ≤ y  ≤ 1) cathodes is studied for which the only redox‐active species is vanadium. While X‐ray diffraction (XRD) confirms the formation of solid solutions between the y  = 0 and 1 end members, X‐ray absorption spectroscopy and solid‐state nuclear magnetic resonance reveal a complex evolution of the local structure upon progressive Mg 2+ substitution for V 3+ . Concurrently, the intercalation voltage rises from 3.35 to 3.45 V, due to increasingly more ionic VO bonds, and the sodium (de)intercalation mechanism transitions from a two‐phase for y  ≤ 0.5 to a solid solution process for y  ≥ 0.5, as confirmed by in operando XRD, while Na‐ion diffusion kinetics follow a nonlinear trend across the compositional series. Abstract : A series of NASICON‐Na3+ y V2− y Mg y (PO4 )3 (0 ≤ y ≤ 1) cathodes is synthesized, which shows complex local structural evolution upon progressive Mg 2+ substitution. Accordingly, these cathodes display changes in their intercalation voltages, sodium (de)intercalation mechanism, and charge/discharge polarization values as y varies.